Bacterial complications after liver transplantation. Promising directions for further research - U. R. Salimov; A. E. Shcherba; O. O. Rummo (Трансплантология (Москва), 2023)
This article is presented in form of a current literature review on bacterial complications of the early post-liver transplantation period and promising areas for studying the effect of bacterial flora in patients after liver transplantation. The paper describes the problem of the emergence, spread, and pathogenesis of various bacterial complications, as well as current concepts of various bacterial complication’s impact on the results of liver transplantation. The results of ventilatorassociated pneumonia in patients after liver transplantation are given. A theoretical analysis of bacterial complications from the standpoint of microbiota effects on the biliary tree was carried out. The review also highlights a relatively new conceptual approach in examining the results of scientific research using the "Machine Learning Method”. The so-called CDC “Big Four” was chosen as the main infectious nomenclature in this article. However, catheter-associated bacterial complications, which pathogenesis has been sufficiently studied to date, have been replaced by a relatively new group of complications – bacteriobilia. This review also contains a brief statistical data collected in the frames of the NCT04281797 study. Own cohort data consisted of 57 patients who underwent orthotopic liver transplantation from a post-mortem donor. Surgical site infection was the most common bacterial complication of the early postoperative period. The most common causative agent of bacterial infection was Klebsiella pneumonia and Enterococcus.